Heterogeneidade industrial regional: Um comparativo entre as UFs da regi\~ao Centro-Oeste e S\~ao Paulo - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– The economies of the Midwest region, since the 1990s, have been undergoing a change in their development style, as external factors have become more pulsating vis-à-vis internal factors as determinants in the transformation of productive structures of this regional space. More connected to international markets, these local economies accelerated the process of modernizing their productive structures, but without breaking with their condition of underdevelopment. It is in this context that the whole plot of this investigation is woven, that is, to verify whether there is any reduction in the gap between the average labor productivity of the industrial sectors due to competitiveness factors in the states that form the Midwest region vis-à-vis the state of S\~ao Paulo in the period from 1996 to 2016. For this purpose, the historical-structural method is adopted as a means to test and validate the empirical evidence that the average productivity differential of the industrial sectors due to centralostatic competitiveness factors vis-à-vis -vis to the state of S\~ao Paulo has been decreasing in the interstitium from 1996 to 2016. In this sense, the industrial sectors due to competitiveness factors in the Midwest region that showed greater convergence in terms of industrial labor productivity vis-à-vis the state from S\~ao Paulo were those based on natural resources, differentiated, intensive in scale and intensive in work. With the exception of the Federal District, no state in the Midwest showed a reduction in the gap between the productivity differential of industrial work vis-à-vis the state of S\~ao Paulo in what concerns the science-based sector. Thus, it is important to underline that the degree of heterogeneity between the industrial sectors that constitute the states of the Midwest and S\~ao Paulo presented, in the interstitium from 1996 to 2016, a decline, since their values were closer to the average of each signaling, therefore, that the diffusion of technical progress has followed the path of greater interregional homogenization. However, it is important to emphasize that this did not mean that these states have overcome the duality between the companies that modernized and those that still remained clinging to the fetters of archaic and traditional techniques. This reinforces the technological dependence of this regional space in relation to the technological standard established in the central countries, since the states of the Midwest region have little capacity for endogenous generation of science, technology and innovation (CT&I). This fact reinforces the need to formulate state strategies in science, technology and innovation (ST&I) to reduce the dependence of these states vis-à-vis the technological innovations that are produced in central countries.
Keywords: R11; 330; technical progress; structural heterogeneity; Midwest